Impact of Superoxide Dismutase Mimetic AEOL 10150 on the Endothelin System of Fischer 344 Rats. - Devi Ganesh; Prem Kumarathasan; Errol M Thomson; Carly St-Germain; Erica Blais; James Crapo; Renaud Vincent (PLoS ONE, 2016)
Endothelin-1 is a potent vasoconstrictor and mitogenic peptide involved in the regulation of vasomotor tone and maintenance of blood pressure. Oxidative stress activates the endothelin system, and is implicated in pulmonary and cardiovascular diseases including hypertension, congestive heart failure, and atherosclerosis. Superoxide dismutase mimetics designed with the aim of treating diseases that involve reactive oxygen species in their pathophysiology may exert a hypotensive effect, but effects on the endothelin system are unknown. Our objective was to determine the effect of the superoxide dismutase mimetic AEOL 10150 on the basal endothelin system in vivo. Male Fischer-344 rats were injected subcutaneously with 0, 2 or 5 mg/kg body weight of AEOL 10150 in saline. Plasma oxidative stress markers and endothelins (bigET-1, ET-1, ET-2, ET-3) as well as lung and heart endothelin/nitric oxide system gene expressions were measured using HPLC-Coularray, HPLC-Fluorescence and RT-PCR respectively. AEOL 10150 reduced (p<0.05) the circulating levels of isoprostane (-25%) and 3-nitrotyrosine (-50%) measured in plasma 2h and 24h after treatment, confirming delivery of a physiologically-relevant dose and the potent antioxidant activity of the drug. The reduction in markers of oxidative stress coincided with sustained 24h decrease (p<0.05) of plasma levels of ET-1 (-50%) and ET-3 (-10%). Expression of preproET-1 and endothelin converting enzyme-1 mRNA were not altered significantly in the lungs. However preproET-1 (not significant) and ECE-1 mRNA (p<0.05) were increased (10-25%) in the heart. Changes in the lungs included decrease (p<0.05) of mRNA for the ET-1 clearance receptor ETB and the vasoconstriction-signaling ETA receptor (-30%), and an early surge of inducible nitric oxide synthase expression followed by sustained decrease (-40% after 24 hours). The results indicate that interception of the endogenous physiological flux of reactive nitrogen species and reactive oxygen species in rats impacts the endothelin/nitric oxide system, supporting a homeostatic relationship between those systems.